1999
DOI: 10.1046/j.1440-1681.1999.02982.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Functional Effects of Carbachol and Ischaemic Preconditioning in Rat Isolated Heart

Abstract: 1. Metabolic and functional effects of ischaemic preconditioning (IP), pretreatment with carbachol (Ch) and combined interventions were studied in rat isolated working hearts subjected to 20 min global ischaemia (37 degrees C) and 40 min reperfusion. Prior to the ischaemic period, hearts were either perfused according to Langendorff (control group), ischaemically preconditioned by 5 min global ischaemia and 5 min reperfusion (IP group), perfused with 0.1 mumol/L Ch for 5 min and then with Ch-free Krebs'-Hensel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
1
3
0
1
Order By: Relevance
“…Trimetazidine did not alter the mean arterial blood pressure or heart rate. Pretreatment with carbachol causes a delay in cell necrosis similar to ischemic preconditioning [13]. In addition to arrhythmias and infarct size, trimetazidine markedly reduce plasma MDA and lactate levels as shown in the present study.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Trimetazidine did not alter the mean arterial blood pressure or heart rate. Pretreatment with carbachol causes a delay in cell necrosis similar to ischemic preconditioning [13]. In addition to arrhythmias and infarct size, trimetazidine markedly reduce plasma MDA and lactate levels as shown in the present study.…”
Section: Discussionsupporting
confidence: 80%
“…Ischemic preconditioning is mediated via several sarcolemmal receptors, which are mostly linked to inhibitory G-protein as seen with muscarinic M 2 receptor agonist carbachol [9]. Pretreatment with carbachol causes a delay in cell necrosis similar to ischemic preconditioning [13]. Carbachol is able to mimic ischemic preconditioning by reducing infarct size and delaying occurrence of VT and VF during ischemia in rat hearts [9].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac pump function was assessed by minute volume and aortic output; stroke was calculated as cardiac output/ HR. Coronary resistance was calculated as AP/coronary flow [18].…”
Section: Heart Perfusionmentioning
confidence: 99%
“…Ischaemic stress was studied by Pisarenko, Shulzhenko & Studneva (1999). The authors found that ischaemia (20 min global ischaemia) caused decrease in aortic output, cardiac output and stroke volume that was reversible by carbachol and ischaemic preconditioning.…”
Section: Hypoxiamentioning
confidence: 99%